Анализ энергетической эффективности электроприводов пассажирских лифтов - Андрющенко, Олег Андреевич; Бойко, Андрей Александрович; Бабийчук, Ольга Борисовна (НТУ "ХПИ", 2010)
The power efficiency analysis of the adjustable electric various systems drive of passenger lifts is given in work. The power efficiency is estimated on efficiency of the mechanism at rise of a nominal cargo and in a mode of start-up. The results of the analysis prove to be true by accounts of expenses and energy losses at improvement of morning and evening works cycles of the lift in view of the passengers flow. The progressiveness of gearless electric drive, in particular with thyratron motor of direct current with a disk rotor is shown. For the engineers and science officers engaged in development and modernization of electric drives of passenger lifts.
The analysis of electric drives power efficiency of passenger lifts
Keywords: редуктор механический; КПД; ротор; преобразователь частоты; напряжение; преобразователь широтно-импульсный; шкив